Annual Plan 1970-71 (Statistical Details) - Government of Himachal Pradesh (Government of Himachal Pradesh, 1971)
The Annual Plan for 1970–71 prepared by the Planning and Evaluation Department, in conjunction with the objectives of the Fourth Five-Year Plan, outlines a comprehensive strategy for economic development through targeted investments across key sectors such as agriculture, irrigation, power, industry, infrastructure, and social services. With a total projected outlay of approximately Rs. 1,705 million, the plan prioritizes agricultural production and rural development by allocating significant resources to programs such as minor irrigation, soil conservation, animal husbandry, and agricultural infrastructure aimed at increasing productivity and improving rural livelihoods. Substantial funding is also directed toward irrigation and power projects, including flood control measures and hydroelectric initiatives such as the Giri and Uhl Hydel projects, which are designed to expand energy generation capacity and support industrial growth. Infrastructure development forms a central component of the plan, with major allocations to transport and communication networks to improve road connectivity and facilitate economic activities across the region. The plan further emphasizes the development of industry and mining through financial support to large, medium, and small-scale industries, as well as initiatives promoting mineral resource utilization and industrial corporations. Social services receive considerable attention through investments in health, education, housing, drinking water supply, and welfare programs aimed at supporting disadvantaged communities and enhancing the overall quality of life. In addition to financial allocations, the plan outlines employment generation strategies and labor requirements across major projects, highlighting the need for both skilled and unskilled workers in infrastructure and energy development projects. Agricultural production targets, particularly for key crops such as rice and wheat, are supported by the promotion of high-yielding varieties and improved irrigation coverage to maximize productivity. Cooperative institutions and training programs are also encouraged to strengthen agricultural and industrial capacity, improve resource management, and foster community participation in development initiatives. Overall, the Annual Plan and Fourth Plan framework represent an integrated development approach that combines infrastructure expansion, agricultural modernization, industrial promotion, and social welfare programs to stimulate economic growth, create employment opportunities, and establish a sustainable foundation for long-term regional development.
Planning & Evaluation Department Government of Himachal Pradesh
Planning & Evaluation Department Government of Himachal Pradesh
Keywords: State Annual Plan; Agricultural Production Programs; Irrigation and Flood Control Projects; Hydroelectric Power Development; Transport and Communication Infrastructure; Industry and Mining Development; Social Services and Welfare Programs; Rural Development Initiatives; Employment and Labor Requirements; Cooperative Development Programs; Economic Infrastructure Investment